2000
DOI: 10.1677/erc.0.0070085
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy in epithelial ovarian cancer.

Abstract: Although epidemiologic studies, animal experiments and receptor studies have shown that not only normal ovaries but also many malignant ovarian tumors can be considered as endocrine related and hormone dependent, the place of hormonal therapy in the management of patients with ovarian cancer remains unsettled. Most trials of hormonal treatment in ovarian cancer have been retrospective, involved only limited numbers of patients, and lacked important patient-related data and information pertaining to tumor chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 71 publications
0
43
0
5
Order By: Relevance
“…Monotherapy studies using tamoxifen, aromatase inhibitors, and GnRH analogues had yielded variable results with objective response rates ranging between 0 and 56%. 17,[19][20][21][34][35][36][37][38] Combinatorial treatment regimens combining tamoxifen and goserelin or tamoxifen and Gefitinib had obtained results with objective response rates of up to 11.5%. 39,40 Few of these studies had selected patients based on the immunohistochemically determined estrogen receptor status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monotherapy studies using tamoxifen, aromatase inhibitors, and GnRH analogues had yielded variable results with objective response rates ranging between 0 and 56%. 17,[19][20][21][34][35][36][37][38] Combinatorial treatment regimens combining tamoxifen and goserelin or tamoxifen and Gefitinib had obtained results with objective response rates of up to 11.5%. 39,40 Few of these studies had selected patients based on the immunohistochemically determined estrogen receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, concerning tamoxifen, it has not been definitely clarified whether it only acts as a pure estrogen antagonist in ovarian tissue, or it has also an agonist effects. [17][18][19][20][21] In breast cancer, we had recently described estrogen receptor-a (ESR1) gene amplification as a frequent mechanism for estrogen receptor overexpression. More than 20% of breast cancers showed ESR1 gene amplification and more than 15% additional cases low-level ESR1 gene copy number gains.…”
mentioning
confidence: 99%
“…Despite the expression of ER in approximately 60% of epithelial ovarian cancers (Havrilesky et al, 2001;Rao and Slotman, 1991), only 5 Ā± 18% women clinically respond to the antiestrogen tamoxifen (Hatch et al, 1991;Ahlgren et al, 1993;Makar, 2000). However, most studies are retrospective and have been designed as second line therapy of resistant or recurrent disease after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of experimental and clinical studies suggest a role of estrogens in ovarian carcinogenesis (Rao and Slotman, 1991;Makar, 2000). A recent prospective cohort study involving 211 000 postmenopausal women showed an increased risk of ovarian cancer mortality in women who used estrogen replacement therapy for 10 or more years (Rodriguez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%